The Conceptual Structure of Emotional Support in HIV Care - McEwan, Laura (2009)
This study was conducted to clarify and conceptualise the term ‘emotional support’ in HIV care delivery. Increasingly in recent years the focus in nursing has been on holistic care, in which emotional support is an integral phenomenon. In HIV care there are many issues related to chronic illness and HIV related stigma which give rise to complex emotional needs that need to be addressed by nurses. It is acknowledged in the literature that emotional support is an elusive concept which has limited definitions, little evidence to distinguish from other concepts and difficulties in measurement.